2005
DOI: 10.1080/01468030590922975
|View full text |Cite
|
Sign up to set email alerts
|

Arc-Induced Long-Period Gratings

Abstract: The electric arc technique allows the inscription of long-period gratings (LPGs) virtually in all types of fibers, including non-photosensitive fibers, the case of non-Gedoped photonic crystal fibers being of particular interest. LPGs written in standard fibers using this technique have shown a high thermal stability. Also, the resistance to γ -radiation of LPGs arc-induced in pure-silica-core fibers is being assessed and the achieved results are very promising. We have also demonstrated that the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 43 publications
0
61
0
1
Order By: Relevance
“…The techniques commonly used for inscription of LPGs are based on induced changes in the refractive index of the fiber core through electric discharge, exposition UV light and CO 2 laser [14][15][16], or by formation of microbendings in the fiber [17].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques commonly used for inscription of LPGs are based on induced changes in the refractive index of the fiber core through electric discharge, exposition UV light and CO 2 laser [14][15][16], or by formation of microbendings in the fiber [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both methods, to obtain the localized heating of the fiber, rely on a point-by-point writing approach and therefore they inherit the advantageous flexibility already mentioned. Also for these techniques there are several mechanisms that contribute to the refractive index modulation: relaxation of frozen stresses during fiber drawing, physical deformation, glass compaction or expansion, core dopants diffusion, among which the predominant cause depends on the heating treatment, the fiber type and any mechanical stress applied (Rego et al, 2005a;Y. Wang, 2010).…”
Section: Long Period Gratings: a View Backmentioning
confidence: 99%
“…The electric arc technique is among the few techniques able to produce gratings that can withstand temperatures of the order of 10008C. In past years, the subject of arc-induced gratings and their applications was intensively investigated, namely, long period fibre gratings (LPFGs) were inscribed in different types of fibre, their temperature behaviour was investigated up to 12008C and distinct behaviour was observed for Ge-doped and Ge-free fibres [1]. It was also demonstrated that arc-induced gratings can withstand temperatures of 12008C for short periods.…”
mentioning
confidence: 99%